The Role of Religious Service Attendance, Psychosocial and Behavioral Determinants of Antiretroviral Therapy (ART) Adherence: Results from HPTN 063 Cohort Study. - Ransome, Yusuf; Mayer, Kenneth H.; Tsuyuki, Kiyomi; Mimiaga, Matthew J.; Rodriguez-Diaz, Carlos E.; Srithanaviboonchai, Kriengkrai; Friedman, Ruth K.; Limbada, Mohammed; Safren, Steven A.; for the HIV Prevention Trials Network 063 Team (AIDS & Behavior, 2019)
Early and sustained antiretroviral therapy (ART) adherence can suppress the HIV virus in individuals and reduce onward transmission of HIV in the population. Religiosity has been associated with better HIV clinical outcomes. Data are from a longitudinal, observational study of 749 HIV-infected individuals from Brazil, Zambia, and Thailand (HPTN 063). Ordered logistic regression assessed whether religious service attendance was associated with ART adherence (self-reported and plasma HIV-RNA) and moderated the association between alcohol problems and ART adherence. In each country, > 80% of participants reported high self-reported ART adherence (good/very good/excellent). Religious service attendance exceeded 85% but was statistically unrelated to adherence. In combined-country models, (p = 0.03) as alcohol problems increased, the probability of high self-reported ART adherence, as well as viral-load, became weaker at higher compared to low service attendance frequency. Future studies should evaluate spirituality variables and replicate the moderation analyses between religious attendance and alcohol problems.